A carboxymethyl lentinan layer by layer self-assembly system as a promising drug chemotherapeutic platform. (1st June 2021) - Cai, Duanhua; Shi, Linrong; Long, Ruimin; Ren, Gang; Wang, Shibin; Liu, Yuangang
Highlights: A novel carboxymethyl lentinan layer-by-layer self-assembly system was constructed. This system proposed an efficient strategy for improving MSN-based carrier platform. The improved properties include biocompatibility, drug loading and cell interaction. This system enlarges the application of lentinan for future cancer therapy. Abstract: Surface functionalization of mesoporous silica nanoparticles (MSNs) has been proposed as an efficient strategy for enhancing the biocompatibility and efficiency of an MSN-based carrier platform. Herein, natural polyelectrolyte multilayers composed of poly-l -ornithine (PLO) and carboxymethyl lentinan (LC) were coated on the surface of MSNs through a layer-by-layer (LbL) self-assembly technique, and were characterized by ζ-potential, FTIR, 13 C NMR, SEM, TEM, XRD, and TG. The prepared carrier presented alternating positive and negative potentials when coated with the polyelectrolytes, and the surface of MSN-PLO/LC was rougher compared to the naked MSNs. The biocompatibility tests, including cytocompatibility, hemocompatibility, and histocompatibility, showed that MSNs biocompatibility could be improved by modifying LC. A high loading and sustained release drug delivery system was constructed after loading doxorubicin (DOX) into the prepared MSN-PLO/LC, which exhibited significant anti-proliferative efficiency in human cervical cancer cell lines (Hela). Therefore, the PLO/LC LbL NPs (layer-by-layer self-assembled nanoparticles coated with PLO/LC layers) based on MSNs, which is easily prepared by electrostatic interactions, can be considered a promising drug chemotherapeutic platform and delivery technique for future human cervical cancer therapy.